Prevention of venous reflux with full utilization of venoplasty in lymphaticovenular anastomosis. Issue 3 (March 2020) - Akita, Shinsuke; Yamaji, Yoshihisa; Tokumoto, Hideki; Maei, Haruka; Tezuka, Takafumi; Ogata, Hideyuki; Kosaka, Kentaro; Kubota, Yoshitaka; Kuriyama, Motone; Mitsukawa, Nobuyuki
Summary: Background: Intraoperative retrograde blood flow from the vein to the lymphatic vessels in lymphaticovenular anastomosis (LVA) for lower extremity lymphedema (LEL) leads to poor results. This study aimed to establish a treatment strategy to control venous reflux in LVA. Methods: A unified strategy to prevent venous reflux was used in 95 limbs (study group). Dilated perforating veins were ligated, and LVA at the small branch of the ligated vein was considered. External valvuloplasty in the small vein was performed to eliminate venous reflux pre- and post-LVA. A Y-shaped venoplasty for the relatively large vein was considered in cases without adequate-sized vein stump with a functional valve. The results were compared with the 34 limbs undergoing conventional multiple LVAs (control group). Results: Intraoperative venous reflux and postoperative ecchymosis significantly decreased in the study group (0/462 anastomosis vs. 15/148 anastomosis, p < 0.0001 and 0/81 patients vs. 3/25 patients, p = 0.01, respectively). The average frequency of cellulitis during a year following LVA was significantly smaller in the study group than in the control group (0.05 ± 0.03 vs 0.20 ± 0.06, p = 0.04).The amount of improvement in the LEL index a year after LVA was significantly larger in the study group than in the control group (22.2 ± 9.6 vs. 18.3 ± 9.8, p = 0.04). Conclusion: Using the new strategy developed in this study, venous reflux could be completely prevented, and stable clinical results were obtained in patients with LEL. Prevention of venous reflux with full utilization of venoplasty might improve the LVA result.